ETHNOBOTANICAL ACCOUNT OF MEDICINAL PLANTS USED BY THE INHABITANTS OF ARUMANALLOOR PANCHAYAT OF KANNIYAKUMARI, TAMILNADU, INDIA - Ani Besant S2* Anami Augustus Arul A1 Blessy R2 Catherine Sheeja V2 Hanna Jeeja Alexander2, (Chelonian Research Foundation, 2023)
Plants are used to treat and prevent diseases in a different way. As a result, the purpose of this paper is to document the traditional knowledge of medicinal plants from the Arumanalloor panchayat of Kanniyakumari District which may be used by the local inhabitants to treat a variety of diseases. In total, 83 plant species representing 69 genera and 36 families have been documented. Herbs are commonly used by the people and trees as well. Nearly 43% of the collected medicinal plants were consumed from the leaves. Hence, this study emphasizes the potential of ethnomedicinal surveys and the need to document traditional ecological knowledge concerning the use of medicinal plants.